1989
DOI: 10.1002/eji.1830190619
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of lymphocyte subsets in the adult rat: a comparison of different lymphoid organs

Abstract: Adult, male Lewis rats received a single injection of 5-bromo-2'-deoxyuridine (BrdUrd) i.v. to label proliferating cells in the S phase of the cell cycle. After 1 and 24 h the thymus, bone marrow, blood, spleen, peripheral, cervical and mesenteric lymph nodes as well as Peyer's patches were removed. In cell suspensions surface staining was performed for B, T, T helper (Th) and cytotoxic/suppressor (Tc/s) T lymphocytes by identifying kappa light chain, CD5+, CD4+ and CD8+ cells, respectively. On the same slide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…Moreover, previous observations in the adult rat had shown that T cells proliferate in the BM more than in other lymphoid organs, thymus excluded (36).…”
mentioning
confidence: 83%
“…Moreover, previous observations in the adult rat had shown that T cells proliferate in the BM more than in other lymphoid organs, thymus excluded (36).…”
mentioning
confidence: 83%
“…A secondary antibody (Z259) and an alkaline phosphatase anti-alkaline phosphatase complex (APAAP, both Dako, Hamburg, Germany) were used with fast blue as substrate. Any BrdU that had been incorporated by the cells was detected in a second step after denaturation of the DNA using formamide/sodium hydroxide, a monoclonal antibody (MoAb) against BrdU (Becton Dickinson, Heidelberg, Germany) and the immunoperoxidase method (Z259 and PAP-complex: Dako) [21]. This resulted in double labelling with subsets in blue and BrdU in brown.…”
Section: Methodsmentioning
confidence: 99%
“…28 One hour and 24 hours after BrdU injection the animals were anesthetized and exsanguinated via the abdominal aorta. Blood, both femora, and the mesenteric lymph nodes were removed for further processing.…”
Section: Identification Of Proliferating B Cells In Bone Marrow Bloomentioning
confidence: 99%
“…The femora were flushed with medium and cytospots were prepared for blood and bone marrow as described. 28 Both on cytospots and on cryostat sections 2 antigens were simultaneously revealed to identify proliferating B cells as described. 29 B cells were identified using the appropriate antibodies (His14, 25 IgM, and IgD 20 ) and visualized in blue.…”
Section: Identification Of Proliferating B Cells In Bone Marrow Bloomentioning
confidence: 99%